(untitled) (Research, Society and Development, 2025)
The objective of this study is to analyze the association of sociodemographic and behavioral factors with insomnia among university students. The hypothesis is that sociodemographic and behavioral factors, such as lifestyle habits and irregularities in the sleep-wake cycle, influence the incidence of sleep disorders such as insomnia. A descriptive cross-sectional study was conducted, with primary data collection in 2023 using a sociodemographic and behavioral questionnaire, combined with a specific scale for diagnosing and monitoring insomnia (the Athens Scale). The total participants were 275 students who met the criteria for being over 18 years old and actively enrolled in undergraduate Pedagogy programs at a State University in northeastern Brazil. The data were statistically analyzed using SPSS. The results demonstrated a significant association between insomnia and the following factors: female gender, anxiety symptoms, use of sleeping pills, and lack of regular physical activity. These findings may encourage the academic community to develop more effective interventions to improve the health and performance of college students.